Development of SAC–OCDMA in FSO with multi-wavelength laser source - Moghaddasi, Majid; Mamdoohi, Ghazaleh; Muhammad Noor, Ahmad Shukri; Mahdi, Mohd Adzir; Ahmad Anas, Siti Barirah (Elsevier, 2015)
We propose and demonstrate a free space optical network, based on spectral amplitude coding optical code division multiple access (SAC–OCDMA) with a multi-wavelength laser source. A detailed theoretical analysis that represents the characteristics of SAC–OCDMA system was developed. In addition to the impact of turbulence, influences of several system noises such as optical beat interference (OBI), relative intensity noise, and receiver noises, have been studied. From the numerical results, it was found that the influence of OBI is more dominant, especially at higher received power. Two different codes, namely, modified quadratic congruence and modified double weight, are then compared with the latter which provides better performance. A transmission distance of 2.6 km with 10 users and an 8 cm aperture diameter is advisable whenever the turbulence is moderate. These results can be improved when a beam divergence smaller than 1 mrad is utilized.